Chapter 4 Globalisation, mobility and labour in African diasporic fiction - Toivanen, Anna-Leena (Taylor & Francis, 2019)
This chapter addresses the entanglement of mobility and labour in the global era, and suggests potential ways to study these issues in contemporary African diasporic fiction.